ChemInform Abstract: Luminescence Properties of a Novel Reddish Orange Long‐Lasting Phosphorescence Phosphor Zn2P2O7:Sm3+, Li+. Issue 50 (December 2015) - Pang, Ran; Sun, Wenzhi; Fu, Jipeng; Li, Haifeng; Jia, Yonglei; Li, Da; Jiang, Lihong; Zhang, Su; Li, Chengyu
Abstract: Zn1.998‐x P2 O7 :Sm0.002, Lix (x = 0.002, 0.02‐0.2) co‐doped phosphors are prepared by solid state reaction of stoichiometric mixtures of ZnO, NH4 H2 PO4, Li2 CO3, and Sm2 O3 in air (alumina crucible, 1.